On conditioned and directed freedom of contrats between business entity - Đurđević Marko; Pavić Dragan (Anali Pravnog Fakulteta u Beogradu)
The term conditioned freedom of contracts appeared in our legal theory before the adoption of the Obligations Relations Act, whereas the term directed freedom of contracts occurred after the Act's entry into force. Both terms were used to signify transformation of freedom of con tracts within the legal system based on ideology of socialism, social ownership of the means of production and government ruled economy and, afterwards, 'coordinated economy'. Conditioned freedom of contracts originated from the right to use the means of production in social ownership. This right, which belonged to social (state-owned) companies, consisted of two components. The first, public-law component conditioned the second, private law component, by means of norms in individual administrative acts and administrative regulations. As these norms were an expression of state power, they make the contract subordinate: individual administrative act is a condition for the conclusion of contract, and administrative regulations for its validity. Directed freedom of contracts is freedom of making contracts directed by economic order established by the Constitution, systemic laws, and partially by the norms of the basic principles of the Obligations Relations Act which are related to social companies. As regards freedom of contracts it can be said that even today it is directed by legal principles and norms of economic-legal public policy through which the state interferes in business enterprises.